Modernizing America’s National Forest Inventory through a Third Blue Ribbon Panel - Aaron Weiskittel; Dale Hogg; John W. Coulston; Christopher W. Woodall; Holly L. Munro; Hailemariam Temesgen; Timothy Foley; Nathaniel Osborne; Nathaniel Naumann; James Rakestraw; John S. Gunn; Nadia Tase; et al. (Journal of Forestry, 2026)

Changing how you look at climate change: attention bias modification increases attention to climate change - Joshua M. Carlson; Madeline Voltz; John Foley; Lisa Gentry; Lin Fang (Climatic Change, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Dynamic Response of the Thoracolumbar and Sacral Spine to Simulated Underbody Blast Loading in Whole Body Post Mortem Human Subject Tests - Donald Sherman; Karthik Somasundaram; Paul Begeman; Sierra Foley; Jason Greb; Cynthia Bir; Constantine K. Demetropoulos; John M. Cavanaugh (Annals of Biomedical Engineering, 2021)

Pharmacokinetic/Pharmacodynamic Modeling of a Cell-Penetrating Peptide Phosphorodiamidate Morpholino Oligomer in mdx Mice - Marie Claire Mukashyaka; Chia-Ling Wu; Kristin Ha; Jianbo Zhang; Jenna Wood; Samantha Foley; Bryan Mastis; Nino Jungels; Huadong Sun; Mohammad Shadid; Shawn Harriman; John R. Hadcock (Pharmaceutical Research, 2021)
Purpose Peptide-conjugated phosphorodiamidate morpholino oligomers (PPMOs) have shown promise in treating Duchenne muscular dystrophy (DMD). We evaluated a semi-mechanistic pharmacokinetic (PK) and pharmacodynamic (PD) model to capture the relationship between plasma and muscle tissue exposure/response in mdx mice treated by mouse surrogate PPMO. Methods A single or repeated (every 4 weeks for 20 weeks) intravenous PPMO dose was administered to mdx mice (n = 6/timepoint). A PK/PD model was built to characterize data via sequential modeling. A 2-compartment model was used to describe plasma PK. A simultaneous tissue PK/PD model was subsequently developed: 2-compartment model to describe muscle PK; linked to an indirect response model describing stimulation of synthesis of skipped transcript, which was in turn linked to stimulation of synthesis of dystrophin protein expression. Results Model performance assessment via goodness-of-fit plots, visual predictive checks, and accurate parameter estimation indicated robust fits of plasma PK and muscle PK/PD data. The model estimated a PPMO tissue half-life of 5 days—a useful parameter in determining the longevity of PPMOs in tissue and their limited accumulation after multiple doses. Additionally, the model successfully described dystrophin expression after single dosing and associated protein accumulation after multiple dosing (increasing ~ twofold accumulation from the first to last dose). Conclusions This first PK/PD model of a PPMO in a DMD disease model will help characterize and predict the time course of PK/PD biomarkers in mdx mice. Furthermore, the model framework can be used to develop clinical PK/PD models and can be extended to other exon-skipping therapies and species.

Drivers of longitudinal telomere dynamics in a long‐lived bat species, Myotis myotis - Nicole M. Foley; Eric J. Petit; Thomas Brazier; John A. Finarelli; Graham M. Hughes; Frédéric Touzalin; Sébastien J. Puechmaille; Emma C. Teeling (Molecular Ecology, 2020)
Age‐related telomere shortening is considered a hallmark of the ageing process. However, a recent cross‐sectional ageing study of relative telomere length (rTL) in bats failed to detect a relationship between rTL and age in the long‐lived genus Myotis ( M. myotis and M. bechsteinii ), suggesting some other factors are responsible for driving telomere dynamics in these species. Here, we test if longitudinal rTL data show signatures of age‐associated telomere attrition in M. myotis and differentiate which intrinsic or extrinsic factors are likely to drive telomere length dynamics. Using quantitative polymerase chain reaction, rTL was measured in 504 samples from a marked population, from Brittany, France, captured between 2013 and 2016. These represent 174 individuals with an age range of 0 to 7+ years. We find no significant relationship between rTL and age ( p = .762), but demonstrate that within‐individual rTL is highly variable from year to year. To investigate the heritability of rTL, a population pedigree ( n = 1744) was constructed from genotype data generated from a 16‐microsatellite multiplex, designed from an initial, low‐coverage, Illumina genome for M. myotis . Heritability was estimated in a Bayesian, mixed model framework, and showed that little of the observed variance in rTL is heritable ( h 2 = 0.01–0.06). Rather, correlations of first differences, correlating yearly changes in telomere length and weather variables, demonstrate that, during the spring transition, average temperature, minimum temperature, rainfall and windspeed correlate with changes in longitudinal telomere dynamics. As such, rTL may represent a useful biomarker to quantify the physiological impact of various environmental stressors in bats.

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

The Kraken in the Aquarium: Questions that Urgently Need to be Addressed in Order to Advance Marine Conservation - John A. Cigliano; Amy Bauer; Megan M. Draheim; Melissa M. Foley; Carolyn J. Lundquist; Julie-Beth McCarthy; Katheryn W. Patterson; Andrew J. Wright; E. C. M. Parsons (Frontiers in Marine Science, 2016)

Sexual Health Concerns Among Cancer Survivors: Testing a Novel Information-Need Measure Among Breast and Prostate Cancer Patients - Sheila A. Crowley; Sallie M. Foley; Daniela Wittmann; Christina H. Jagielski; Rodney L. Dunn; Patricia M. Clark; Jennifer J. Griggs; Catherine Peterson; Marcia Leonard; Lawrence C. An; John T. Wei; James E. Montie; et al. (Journal of Cancer Education, 2016)

NanoXCT: A Novel Technique to Probe the Internal Architecture of Pharmaceutical Particles - Jennifer Wong; Dexter D’Sa; Matthew Foley; John Gar Yan Chan; Hak-Kim Chan (Pharmaceutical Research, 2014)

Seventy‐One Important Questions for the Conservation of Marine Biodiversity - E. C. M. PARSONS; BRETT FAVARO; A. ALONSO AGUIRRE; AMY L. BAUER; LOUISE K. BLIGHT; JOHN A. CIGLIANO; MELINDA A. COLEMAN; ISABELLE M. CÔTÉ; MEGAN DRAHEIM; STEPHEN FLETCHER; MELISSA M. FOLEY; REBECCA JEFFERSON; et al. (Conservation Biology, 2014)
The ocean provides food, economic activity, and cultural value for a large proportion of humanity. Our knowledge of marine ecosystems lags behind that of terrestrial ecosystems, limiting effective protection of marine resources. We describe the outcome of 2 workshops in 2011 and 2012 to establish a list of important questions, which, if answered, would substantially improve our ability to conserve and manage the world's marine resources. Participants included individuals from academia, government, and nongovernment organizations with broad experience across disciplines, marine ecosystems, and countries that vary in levels of development. Contributors from the fields of science, conservation, industry, and government submitted questions to our workshops, which we distilled into a list of priority research questions. Through this process, we identified 71 key questions. We grouped these into 8 subject categories, each pertaining to a broad component of marine conservation: fisheries, climate change, other anthropogenic threats, ecosystems, marine citizenship, policy, societal and cultural considerations, and scientific enterprise. Our questions address many issues that are specific to marine conservation, and will serve as a road map to funders and researchers to develop programs that can greatly benefit marine conservation. Setenta y Un Preguntas Importantes para la Conservación de la Biodiversidad Marina

10Be, 18O and radiogenic isotopic constraints on the origin of adakitic signatures: a case study from Solander and Little Solander Islands, New Zealand - Fiona V. Foley; Simon Turner; Tracy Rushmer; John T. Caulfield; Nathan R. Daczko; Paul Bierman; Matthew Robertson; Craig D. Barrie; Adrian J. Boyce (Contributions to Mineralogy and Petrology, 2014)

Homozygous truncating PTPRF mutation causes athelia - Guntram Borck; Liat de Vries; Hsin-Jung Wu; Pola Smirin-Yosef; Gudrun Nürnberg; Irina Lagovsky; Luis Henrique Ishida; Patrick Thierry; Dagmar Wieczorek; Peter Nürnberg; John Foley; Christian Kubisch; et al. (Human Genetics, 2014)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Effects of repeated administration of chemotherapeutic agents tamoxifen, methotrexate, and 5-fluorouracil on the acquisition and retention of a learned response in mice - Ellen A. Walker; John J. Foley; Rachel Clark-Vetri; Robert B. Raffa (Psychopharmacology, 2011)

Continuous cratonic crust between the Congo and Tanzania blocks in western Uganda - Klemens Link; Daniel Koehn; Matthias G. Barth; John V. Tiberindwa; Erasmus Barifaijo; Kevin Aanyu; Stephen F. Foley (International Journal of Earth Sciences, 2010)

Induced preference for host plant chemicals in the tobacco hornworm: contribution of olfaction and taste - John I. Glendinning; Cassidy Foley; Irina Loncar; Meelu Rai (Journal of Comparative Physiology A, 2009)

Comprehensive N-Methyl Scanning of a Potent Peptide Inhibitor of Malaria Invasion into Erythrocytes Leads to Pharmacokinetic Optimization of the Molecule - Denis Scanlon; Karen S. Harris; Andrew M. Coley; John A. Karas; Joanne L. Casey; Andrew B. Hughes; Michael Foley (International Journal of Peptide Research and Therapeutics, 2008)

Effects of chemotherapeutic agents 5-fluorouracil and methotrexate alone and combined in a mouse model of learning and memory - John J. Foley; Robert B. Raffa; Ellen A. Walker (Psychopharmacology, 2008)

The global distribution of cultivable lands: current patterns and sensitivity to possible climate change - Navin Ramankutty; Jonathan A. Foley; John Norman; Kevin McSweeney (Global Ecology and Biogeography, 2002)
Aim This study makes quantitative global estimates of land suitability for cultivation based on climate and soil constraints. It evaluates further the sensitivity of croplands to any possible changes in climate and atmospheric CO 2 concentrations. Location The location is global, geographically explicit. Methods The methods used are spatial data synthesis and analysis and numerical modelling. Results There is a cropland ‘reserve’ of 120%, mainly in tropical South America and Africa. Our climate sensitivity analysis indicates that the southern provinces of Canada, north‐western and north‐central states of the United States, northern Europe, southern Former Soviet Union and the Manchurian plains of China are most sensitive to changes in temperature. The Great Plains region of the United States and north‐eastern China are most sensitive to changes in precipitation. The regions that are sensitive to precipitation change are also sensitive to changes in CO 2 , but the magnitude is small compared to the influence of direct climate change. We estimate that climate change, as simulated by global climate models, will expand cropland suitability by an additional 16%, mainly in the Northern Hemisphere high latitudes. However, the tropics (mainly Africa, northern South America, Mexico and Central America and Oceania) will experience a small decrease in suitability due to climate change. Main conclusions There is a large reserve of cultivable croplands, mainly in tropical South America and Africa. However, much of this land is under valuable forests or in protected areas. Furthermore, the tropical soils could potentially lose fertility very rapidly once the forest cover is removed. Regions that lie at the margins of temperature or precipitation limitation to cultivation are most sensitive to changes in climate and atmospheric CO 2 concentration. It is anticipated that climate change will result in an increase in cropland suitability in the Northern Hemisphere high latitudes (mainly in developed nations), while the tropics will lose suitability (mainly in developing nations).

Measurements and Modeling of Carbon and Nitrogen Cycling in Agroecosystems of Southern Wisconsin: Potential for SOC Sequestration during the Next 50 Years - Christopher J. Kucharik; Kristofor R. Brye; John M. Norman; Jonathan A. Foley; Stith T. Gower; Larry G. Bundy (Ecosystems, 2001)